Circadian variation in thoracic impedance - Beckendorf, Claudia; Kirchner, Jens; Paule, Stefan; Achenbach, Stephan; Arnold, Martin (Clinical Research in Cardiology Supplements, 2014)
Introduction: Thoracic impedance (TI) is the electrical resistance measured between the right ventricular shock coil and the can of an implantable cardioverter-defibrillator. As it is known to decrease on lung congestion, it has been proposed as a marker of worsening of cardiac status in heart failure patients. However, the diagnostic value of TI is limited by various confounding factors and the extent of physiologic variability is poorly understood. We therefore analyzed circadian variation of TI. Methods: In 54 patients with an implanted ICD (n = 47) or CRT-D (n = 7) device (85% male, 66 ± 11 years, NYHA class I-IV, EF 31 ± 14 %), TI was measured with an hourly resolution. The resulting 24 TI values per day were transmitted via home monitoring. For each patient, data from an observation interval of 28 days were averaged separately for each time of the day. Intra-day variability was correlated to each individual patient´s daily routine, which was determined by a questionnaire. Results: Daily mean thoracic impedance of all 54 subjects was 61.0 ± 6.2 Ω (range: 43.8-71.8 Ω). Intra-day variation was present in all subjects, ranging from 1.1 to 8.4 Ω and with 3.2 ± 1.7 Ω in average. The typical day-curve (see figure) exhibits a clear minimum in the early morning (average lowest TI: -1.9 ± 1.4 Ω below mean) and a plateau in the afternoon (maximum height: 1.3 ± 1.0 Ω above mean). The phases of the day with large changes in TI - nighttime and morning hours till noon - are strongly correlated with the patients going to bed and getting up from bed, respectively: After both events, TI exhibits a trend in negative respectively positive direction (p < 0.001, Page trend test), which leads to significant changes of TI over at least 6 hours (p < 0.001 for all measurement times, Wilcoxon signed-rank test). Figure: circadian variation of the thoracic impedance of a heart failure patient. Conclusion: Thoracic impedance exhibits a strong circadian variation, which amounts to 7 % of its absolute value and seems to be based on the sleep-wake rhythm. Therefore, daily TI values from a single measurement time per day are prone to errors of the same size, particularly when measured in high-dynamic phases. More appropriate is the use of either the mean or an extremal value of the TI day-curve from several equidistant measurement